2007
DOI: 10.1111/j.1365-2133.2006.07659.x
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime prevalence of self-reported atopic diseases in a population-based sample of elderly subjects: results of the ESTHER study

Abstract: The lifetime prevalence of AD is considerably lower in the elderly compared with the prevalence reported among younger adults in recent studies. Adults with a longer duration of school education appeared to have a higher risk for atopic diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
50
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 18 publications
9
50
1
1
Order By: Relevance
“…Similar to other atopic diseases, the incidence of AD is gradually increasing in countries with aging populations [3,4,5]. The prevalence of AD in our 6,511 analyzed subjects was 1.86%, which agrees with other published data [3,4].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Similar to other atopic diseases, the incidence of AD is gradually increasing in countries with aging populations [3,4,5]. The prevalence of AD in our 6,511 analyzed subjects was 1.86%, which agrees with other published data [3,4].…”
Section: Discussionsupporting
confidence: 81%
“…AD is much less common in adults, especially in the elderly. The prevalence of AD in patients who are 50 years of age or older is estimated to range from 1.5 to 10%; however, different forms of dermatitis exist and some may be caused by IgE reactions [1,2,3,4]. …”
Section: Introductionmentioning
confidence: 99%
“…However, the prevalences of atopic eczema (1.4%) and of acne vulgaris (4.2%) are lower than postulated in the few epidemiological studies [4, 9]. …”
Section: Discussionmentioning
confidence: 94%
“…Thus far, there have been only a few population-based studies of skin diseases so that the available knowledge on the epidemiology of skin diseases is based essentially on studies of selective patient collectives. Correspondingly, the figures on the prevalence of skin diseases vary considerably, for example for psoriasis vulgaris between 1.5 and 2.5% [1], for atopic eczema between 1.5 and 4% in adults and between 4 and 15% in children [2,3,4] and for hand eczema between 1 and 4% in the normal population and between 4.6 and 18% in occupational risk groups [5, 6]. An Italian screening study revealed a prevalence of congenital melanocytic nevi of 0.67% in young men [7].…”
Section: Introductionmentioning
confidence: 99%
“…One study shows that the prevalence of AD in adult and elderly is 1% to 3% [8]. In other study, the prevalence of AD in >50 years old patients is 1.5% to 10% [9].…”
Section: Introductionmentioning
confidence: 99%